Assessment of Genetic Fidelity in Rauvolfia serpentina Plantlets Grown from Synthetic (Encapsulated) Seeds Following in Vitro Storage at 4 °C - Mohammad Anis; Ahmad K. Hegazy; Naseem Ahmad; Mohammad Faisal; Abdulrahman A. Alatar (Molecules, 2012)
An efficient method was developed for plant regeneration and establishment from alginate encapsulated synthetic seeds of Rauvolfia serpentina. Synthetic seeds were produced using in vitro proliferated microshoots upon complexation of 3% sodium alginate prepared in Llyod and McCown woody plant medium (WPM) and 100 mM calcium chloride. Re-growth ability of encapsulated nodal segments was evaluated after storage at 4 °C for 0, 1, 2, 4, 6 and 8 weeks and compared with non-encapsulated buds. Effects of different media viz; Murashige and Skoog medium; Lloyd and McCown woody Plant medium, Gamborg’s B5 medium and Schenk and Hildebrandt medium was also investigated for conversion into plantlets. The maximum frequency of conversion into plantlets from encapsulated nodal segments stored at 4 °C for 4 weeks was achieved on woody plant medium supplement with 5.0 μM BA and 1.0 μM NAA. Rooting in plantlets was achieved in half-strength Murashige and Skoog liquid medium containing 0.5 μM indole-3-acetic acid (IAA) on filter paper bridges. Plantlets obtained from stored synseeds were hardened, established successfully ex vitro and were morphologically similar to each other as well as their mother plant. The genetic fidelity of Rauvolfia clones raised from synthetic seeds following four weeks of storage at 4 °C were assessed by using random amplified polymorphic DNA (RAPD) and inter-simple sequence repeat (ISSR) markers. All the RAPD and ISSR profiles from generated plantlets were monomorphic and comparable to the mother plant, which confirms the genetic stability among the clones. This synseed protocol could be useful for establishing a particular system for conservation, short-term storage and production of genetically identical and stable plants before it is released for commercial purposes.